Suit vintage furniture / Nurul Shahirah Mohd. Zuliadaini ... [et al.] - Mohd Zuliadaini, Nurul Shahirah; Mohd.Noh, Nabilah Natasya; Mahfud Affandi, Nur Asyikin; Mohd. Nasir, Muhammad Imran Arif; Nazam Azhari, Muhammad Zamir; Hashim, Shahril Azman (2015)
As we already know , business plan is one of the tools that required to be prepared in order to open and starting the business. Business plan is written documents which describe the purposed business to be undertaken in the comprehensive and serious manner. It is also known as a project paper, working paper, business proposal or prospectus. A business plan is a written summary of entrepreneur, purpose business venture, it's operational and financial detail, its target market opportunities and strategies, and its manager's skills and ability. The plan serves as an entrepreneurs road map and clue on a journey toward building a successful and ever-lasting business. It described the direction of the company is taking, what its goal are, where it's want the company to be, and how it's going to get there. They are many purposes of business plan as stated below : 1.1. To evaluate the project viability and growth potential 1.2. To apply for loans or financing facilities from the relevant financial institutions 1.3. To act as a guideline for the management of the proposed business 1.4. To allocate business resources effectively Hopefully this plan can be used to convinced and reassured the business achieve the target and give a good profit.